Comorbidity-driven COPD outcomes: the urgent need for full optimisation by respiratory physicians - Sobia Chaudhary; Sundeep Kaul (Clinical Medicine)
Introduction: Chronic obstructive pulmonary disease (COPD) remains a profound global health challenge, characterised by progressive airflow limitation exacerbated significantly by frequently neglected comorbidities. Conditions, such as gastroesophageal reflux disease (GERD), osteoporosis, pulmonary hypertension (PH), bronchiectasis and ischaemic heart disease (IHD), drastically influence patient morbidity, hospitalisations and mortality. Despite compelling evidence underscoring their critical role in disease progression, these comorbidities are consistently underdiagnosed and inadequately managed, necessitating an urgent shift toward a holistic, comorbidity-centred approach in COPD care.1–3 Materials and Methods: A retrospective cohort study was performed involving 500 COPD patients (>60 years), confirmed by spirometry (FEV1/FVC <0.70 post-bronchodilator) and stratified according to Global Initiative for Chronic Obstructive Lung Disease (GOLD)stages. Clinical data, including comorbidities, exacerbation frequency, hospitalisation rates, pulmonary rehabilitation (PR) referrals and mortality, were systematically collected and analysed using descriptive statistics, chi-square tests and logistic regression analyses. Results and Discussion: The study uncovered significant findings emphasising the detrimental role of comorbidities: • GERD prevalence was notable at 20%, significantly increasing COPD exacerbation frequency (p<0.05). Patients with frequent GERD symptoms experienced exacerbations 1.8 times more often annually4; • PH, although present in only 4% of the cohort, carried a strikingly high mortality rate of 31% (p=0.01), marking its devastating prognostic impact5,6; • Bronchiectasis, prevalent in 16% of patients (particularly in GOLD stages 3 and 4), increased hospitalisation rates by 2.3-fold because of recurrent infections, emphasising its crucial role in patient management7; • IHD showed higher prevalence in early COPD stages (GOLD 1: 19.4%, GOLD 2: 23%), yet significantly raised cardiovascular mortality by 21%, underlining the urgent need for integrated cardiopulmonary care2,8; • Osteoporosis was increasingly prevalent in advanced COPD stages, with 28% of osteoporotic patients experiencing fractures, thereby worsening mobility, exacerbations, and survival outcomes3; • Despite proven benefits, pulmonary rehabilitation remained severely underutilised, with only a 37% referral among eligible patients, indicating a substantial gap in adherence to recommended guidelines9,10;Collectively, these results highlight systemic deficiencies in the recognition and management of comorbidities in COPD, strongly suggesting the need for respiratory specialists to proactively lead comprehensive patient care. Conclusion: Our findings compellingly advocate for respiratory physicians to urgently embrace a comprehensive, multidisciplinary approach in COPD management. Routine, proactive screening for GERD, osteoporosis, PH, bronchiectasis and IHD should become a fundamental practice. Effective, structured referral pathways to pulmonary rehabilitation must be established, combined with integrated cardiopulmonary risk assessments and management protocols. Such transformative, comorbidity-centred strategies promise to dramatically reduce preventable exacerbations and hospitalisations, decrease mortality, and substantially enhance patient quality of life.